Pengaruh Konsumsi Manga terhadap Minat Membaca Generasi Z di Indonesia - Muhammad Alif Vidi; Salman Al-Farisi; Tejo Mulyono; Akhdan Ravi Andaman; Pandu Wicaksono; Abiyyu Umar Thoyyib; Nanda Wijaya Putra; Humannisa Rubina Lestari (Khatulistiwa: Jurnal Pendidikan dan Sosial Humaniora, 2024)
This study examines the impact of manga consumption on the reading interest of Generation Z in Indonesia. The research aims to provide insights into how manga reading habits influence overall reading behavior among Generation Z. Using survey methods and statistical analysis, the study employs a quantitative approach to assess the intensity of manga reading and its effect on reading interest. The findings indicate a positive but not significant relationship between manga reading intensity and reading interest. The regression equation Y = 2.117 + 0.316x suggests a 31.6% increase in manga reading intensity for every unit increase in reading interest. However, the regression coefficient is not significant, and the correlation between the variables is weak, with a value of 0.285. These results imply that while there is a positive trend, manga reading intensity does not significantly influence reading interest among Generation Z in Indonesia. This study provides valuable insights for educators and policymakers to develop more effective literacy strategies tailored to Generation Z's reading habits. Keywords: Generation Z, Indonesia, manga, reading interest, reading habits.